Phenology, production and quality of blueberry cultivars - Antunes, Luis Eduardo Corrêa; Gonçalves, Emerson Dias; Ristow, Nara Cristina; Carpenedo, Silvia; Trevisan, Renato (Pesquisa Agropecuaria Brasileira, 2008)
The aim of this work was to evaluate the yield and quality of blueberry cultivars from the rabbiteye group (Bluegem, Bluebelle, Powderblue, Florida, Delite, Briteblue, Climax and Woodard), in Pelotas County, Southern of Rio Grande do Sul State, Brazil, during three growing seasons: 2003/2004, 2004/2005 and 2005/2006. The plants were set in randomized varietal blocks in the orchard, with 16 plants per cultivar, totaling four lines, with two cultivars per line. For statistic analysis of the fruits characteristics, each year of evaluation was considered as one repetition. The characteristics evaluated were the start and the end of fl owering, beginning and end of harvest, mass, longitudinal diameter of fruits, number of fruit per plant, content of total soluble solids, average production by plant, and the estimated productivity per hectare. There was no difference among the cultivars evaluated for the characteristics mass, mean diameter of fruits and levels of total soluble solids. In the region of Pelotas, there is technical viability for growing blueberry, whose cultivars Bluebelle, Briteblue and Bluegem are the most productive.